PERAN UNICEF DALAM PENANGANAN PENGUNGSI ANAK KORBAN KONFLIK SURIAH PADA TAHUN 2015 UNICEF’s Role in The Handling of Child Refugees Victims of Conflict Syria in 2015 - Derinanto (Universitas Muhammadiyah Yogyakarta, 2016)
Non traditional issues in international relations that causing treat of security concept have awaken international society to protect human rights especially for children and women in emergency condition such situation of conflict. where every conflict attenuated victimization are children and women. hance the importance of the role of International Organizations such as UNICEF to address the issue of children as a result of the conflict.His research aim to describing role of UN’s agency, UNICEF in The Handling of Child Refugees Victims of Conflict Syria.The research also explains in detail the root causes of conflict and the consequences of the conflict occurred in the Syria. UNICEF as one of the world institutions that fight for children's rights, has made many changes, working with communities and influencing governments UNICEF has provided significant funding to Handling of Child Refugees Victims of Conflict Syria. UNICEF also strive to connect and engage all parties to the help Refugee child victims of conflict Syria.The technique of data collect in this research is Library Research with descriptive research method. Qualitative data means to give description of roles that given by UNICEF as well as the programmes.